Evaluation of trees and shrubs for oil sands reclamation field trial results - Russell Ecological Consultants (1987)
The Alberta Oil Sands Environmental Research Program (AOSERP) Subproject VE 7.1 was initiated to select suitable tree and shrub species for use in revegetating spoils and tailings resulting from oil sands mining operations in northeastern Alberta. As part of this program three field trials were established near the Mildred Lake field camp, approximately 38 km north of Fort McMurray, in 1980 and 1981. The purpose was to test one or more provenances (seed sources) of promising native and exotic woody species. The trial site was prepared to simulate an oil sands reclamation situation. Overburden and peat were hauled to the site from Syncrude Canada Ltd.’s mining lease and incorporated in native sand. The resulting reconstructed soil was alkaline (pH 7.5), non-saline, and low in available N, P, and K. No fertilizers were added. A fine-mesh fence was erected around the trial site to exclude small mammals. All species were outplanted as one- or two-year-old container stock. All seed used to rear the native species was collected from local populations in the oil sands region. In August 1986 the trials were assessed. Survival rates were high for most species. Girdling damage by small mammals was almost non-existent, probably because of the fine-mesh fencing. Populus Northwest and P. Tristis #1 were the tallest and fastest growing species. Among the native species, Pinus banksiana was the tallest and fastest growing. Several other species also performed well and may be suitable for oil sands reclamation: Caragana arborescens, Cornus stolonifera, Elaeagnus commutata, Empetrum nigrum, Picea glauca, Picea mariana, and Populus Brooks #6. Some species gave mediocre or inconsistent performances, including Betula glandulosa, Betula papyrifera, Populus Walker, and Vaccinium vitis-idaea. The remaining species were failures and may not be adapted to the test site environment: Acer negundo, Alnus tenuifolia/crispa, Elaeagnus angustifolia, Fraxinus pennsylvanica, Lonicera tartarica, Populus tremuloides, Rosa woodsii, Salix ...